Waste management and greenhouse gas emission reduction in Nakhon Si Thammarat municipality through a circular economy municipal solid waste management model - Siriuma Jawjit; Narisara Kaewchutima; Apirak Bumyut (Cleaner Environmental Systems)
Climate change is driven by greenhouse gas (GHG) emissions caused by human activities, of which, improper waste management is a significant source. Thailand aims to reduce its emissions by 30 %–40 % by 2030, identifying the waste sector as crucial for these reductions. Nakhon Si Thammarat (NST) is pivotal in Thailand's waste management efforts due to its major contribution to municipal solid waste (MSW) and its status as the region with the highest amount of improper waste management in the south. This research employed a method for sorting waste composition to analyze waste composition and utilized a community-based participatory research approach, involving community members, researchers, and stakeholders to develop and implement a circular economy MSW management model in five communities within the NST municipality, which is located in the NST province. The results revealed that the majority of waste in the study area consisted of organic and plastic materials. After implementing the model, organic and plastic waste composition were reduced by 6.09 %–11.29 % and 4.18 %–11.11 %, respectively, which also mitigated GHG emissions by 4,234 kgCO2eq/year. In addition, the model could generate an income of 19,537 Baht per year. Despite the model's flexibility and effectiveness, improvements in infrastructure and collaboration with various organizations are needed to support its operation. In conclusion, the study emphasizes that policy support and comprehensive waste management initiatives involving all relevant stakeholders such as government, local authorities, the private sector, and the public are essential for sustainable MSW management.